STRUKTUR LAHIR KUMPULAN PUISI DERU CAMPUR DEBU KARYA CHAIRIL ANWAR - Anggraini, Tri Riya (Lentera: Jurnal Ilmiah Kependidikan, 2017)
This study examines the structure of physic in a collection of poetry Deru Campur Debu by Chairil Anwar. The four poems examined are â€œKepada Peminta-Mintaâ€, â€œSajak Putihâ€, â€œSenja di Pelabuhan Kecilâ€, dan â€œCintaku Jauh di Pulauâ€. The purpose of this study is to describe how the physical structure of four poems in question. The method used is qualitative description. The results show that the poems of Chairil Anwar contain a very rich stylistical element in terms of dictionary selection, imagery, concrete words, figurative language, and rhyme.